Asymptomatic pathogen infection alters interactions at higher trophic levels - Norhayati Ngah; University of Reading . School of Biological Sciences (2018)
Plants and insects have intimate and complex relationships. However, other species, such as plant pathogens, may change the way plants and their herbivores interact. Plant diseases can change the host plant quality, alter physical and physiological traits and defensive capability. These changes can have a consequential effect on insects associated with the infected plant, thus altering interactions between species. However, the effects of these interactions can quantitatively vary amongst individuals and may influenced by many factors including the severity of plant disease (e.g. if the infection is symptomatic or asymptomatic). To date, little is known on the effect of asymptomatic pathogen infection on insects at higher trophic levels. My research aims to examine how patterns of interactions between plants, microbes and insects change when plant pathogen infection is asymptomatic. I examined the effect of asymptomatic plant pathogen infection on the life history and behaviour of herbivorous insects, and its consequent effects on an insect community at higher trophic levels. In the laboratory, I found that asymptomatic pathogen. infection altered plant traits and changed the life history and behaviour of an herbivorous insect and its parasitoid. In the field, the effect of asymptomatic pathogen infection differed between plant varieties and species of insect involved. Asymptomatic pathogen infection greatly affects the assemblage and population dynamics of aphids on one variety of lettuce (Tom Thumb), but no significant effects were found on Little Gem. However, both lettuce varieties were less attractive to natural enemies when asymptomatically infected. The asymptomatic pathogen infection also modulated the interaction of plants and insects on neighbouring plant. More aphids were found on the uninfected plant neighbouring an asymptomatic¬infected plant, and thus influencing the number of natural enemies observed. These findings show the importance of asymptomatic pathogen infection to the ecological interactions at higher trophic levels in the laboratory and field. Pathogen infection, even if asymptomatic, can influence interactions between organisms. This is of considerable interest to both pure and applied ecologists, and can affect the success of biological control programme in agriculture systems.
1. Introduction -- 2. Symptomless host plan infection by the fungal pathogen Botrytis cinerea alters host plan, aphid and parasitoid traits -- 3. Symptomless host plan infection by the pathogen Botrytis cinerea alters the behaviuor of aphids and their natural enemies -- 4. Does asymptomatic infection by the plant pathogen Botrytis cinerea affect the structure of naturally formed insect assemblages? -- 5. Asymptomatic infection by the fungal plant pathogen Botrytis cinerea alters interactions between insect herbivores and their natural enemies in the field -- 6. Both symptomatic and asymptomatic pathogen infection can cause herbivore-mediated indirect interactions between neighbouring plants -- 7. General discussion
Thesis (Degree of Doctor of Philosophy) - University of Reading, 2018
Includes bibliographical references (pages 147-209)
Keywords: University of Reading -- School of Biological Sciences -- Dissertations; Host plants; Host-parasite relationships -- Immunological aspects; Plant diseases